2014
DOI: 10.1097/nmd.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Community Adherence to Schizophrenia Treatment and Safety Monitoring Guidelines

Abstract: The 2003 Schizophrenia PORT treatment recommendations and Mt. Sinai Conference Safety Monitoring recommendations generated guidelines for pharmacological treatment of schizophrenia and monitoring of antipsychotic side effects. This study examined rate of recommendation adherence and impact of adherence on outcomes of outpatients with schizophrenia or schizoaffective disorder in community mental health centers. Clinical practice was assessed as conformant, non-conformant, or not applicable. Treatment practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Despite the evidence that weight gain increases morbidity and mortality and reduces adherence, only one third to half are adequately monitored for the metabolic side effects of antipsychotics. 44 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence that weight gain increases morbidity and mortality and reduces adherence, only one third to half are adequately monitored for the metabolic side effects of antipsychotics. 44 …”
Section: Introductionmentioning
confidence: 99%
“…Although the need for monitoring of patients treated with psychotropic drugs is widely recognized, adherence to monitoring guidelines is often found to be suboptimal . For example, monitoring rates of metabolic parameters such as weight, glucose, and lipids in patients using antipsychotic drugs have been found not to correspond with advice given in CPGs, posing unnecessary risks of morbidity to patients …”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that, while community mental health centers generally conform to the 2003 Patient Outcomes Research Team treatment recommendations, conformance with Mount Sinai Conference recommendations for monitoring somatic health was followed less than 50% of the time. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Reports on the Schizophrenia Patient Outcomes Research Team treatment recommendations and the Mount Sinai Conference Safety Monitoring recommendations suggest that patients in community mental health centers are not adequately monitored by their health care providers for medical comorbidities, including metabolic diseases. 18 Differences between AAs in terms of efficacy and tolerability call for an individualized treatment approach. Although treatment guidelines exist, including the US and International guidelines (American Psychiatric Association 12 and World Federation of Societies of Biological Psychiatry 19 ), it is still not possible to know in advance which antipsychotics are most efficacious for any individual patient; heterogeneity of treatment response results in patients commonly being sequentially treated with different antipsychotic medications in order to find the optimum choice of medication for the individual patient.…”
Section: Introductionmentioning
confidence: 99%